Dlouhodobá péče ve vybraných zemích OECD v kontextu demografických změn - Halásková, Renáta; Halásková, Martina (Univerzita Pardubice, 2017)
With respect to demographic changes and population ageing, all OECD countries will be tackling issues of long-term care (LTC) associated with the need for professional services, collaboration between the formal and informal long-term care systems, and the adjustment of the mix of public and private resources playing part in long-term care financing. The paper aims to evaluate the potential of long-term care in selected OECD countries in connection with population ageing. The majority of the selected countries have seen a rise in the number of long-term care recipients along with total expenditures on long-term care. Nevertheless, these countries differ fundamentally in total expenditures allocated on long-term care per recipient. Results of evaluation using selected indicators of long-term care, by use of two-step cluster analysis, in years 2008 and 2013 also showed a variety of approaches in the provision of long-term care among the analysed countries (mainly in terms of LTC recipients aged 65+ as percentage of total LTC recipients) and in financing of long-term care (mainly in terms of LTC expenditures on institutions as percentage of total LTC expenditures).
Long-term care in selected OECD countries in the context of demographic changes
Keywords: long-term care; long-term care expenditure; recipients of care; demographic changes; population ageing; OECD countries; H41; H51; H75; J11